2015
DOI: 10.1007/s10811-015-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenans from nuclear phases of subantartic Mazzaella laminarioides (Gigartinales, Rhodophyta) and graft copolymerization of alkali-modified carrageenan with acrylamide

Abstract: Aqueous extraction of cystocarpic, tetrasporic, and vegetative individuals of Mazzaella laminariodes collected in the Magellan Ecoregion, Southern Chile, afforded sulfated galactans. Analysis by Fourier transform infrared spectroscopy (FT-IR) and by 1 H and 13 C NMR spectroscopy indicated that purified extracts from cystocarpic (CP) and vegetative individuals (VP) were mixtures of κ/ι-type carrageenans and their precursors μ-and ν-carrageenans, whereas the aqueous extract from tetrasporic individuals was a λ-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
(75 reference statements)
0
9
1
Order By: Relevance
“…The latter improves the gelling properties as reflected by their strength [184][185][186]. By using alkaline hydrolysis or microwave irradiation, carrageenan gels have already been 'cross-linked' with poly(acrylamide) [187][188][189], acrylic acid [190] and methyl methacrylate [191]. In addition, a copolymerization with acrylic acid and 2-acrylamido-2-methylpropane-sulfonic acid has already been performed as well [192].…”
Section: Natural Saps Based On Carrageenan and Its Derivativesmentioning
confidence: 99%
“…The latter improves the gelling properties as reflected by their strength [184][185][186]. By using alkaline hydrolysis or microwave irradiation, carrageenan gels have already been 'cross-linked' with poly(acrylamide) [187][188][189], acrylic acid [190] and methyl methacrylate [191]. In addition, a copolymerization with acrylic acid and 2-acrylamido-2-methylpropane-sulfonic acid has already been performed as well [192].…”
Section: Natural Saps Based On Carrageenan and Its Derivativesmentioning
confidence: 99%
“…Increasing the crosslinking density of SAP will result in a decrease in the space between the polymer chains. A rigid structure is formed which cannot hold large amounts of air (Zhang, et al, 2011;Montaser, et al, 2019;Yu, et al 2011;Kulkarni, et al 2012;Arias, et al 2016). Zhang et al, 2011 reported that more crosslinked networks in polymeric chains occurred, affect a higher crosslinking density and more insoluble copolymers in the water.…”
Section: Results and Discussion Swelling And Tensile Strengthmentioning
confidence: 99%
“…All samples were analyzed with the same size (5 cm x10 cm). SAP films were equilibrated at 27•C and 53% relative humidity in desiccators with silica absorbent for 2 days prior to testing (Arias et al, 2016).…”
Section: Tensile Strengthmentioning
confidence: 99%
“…2012 [46] and Arias et al . 2016 [45] , respectively. The red macroalgae A. chilense and M. laminarioides were collected at Caleta Lenga (Latitude −36.764330°; Longitude −73.173123°) and Caleta Cocholgüe (Latitude −36.590200°; Longitude −72.980159°) respectively, in Biobío Region, Chile.…”
Section: Methodsmentioning
confidence: 99%
“…Exopolysaccharides from P. cruentum and P. purpureum were obtained according to a modified extractive procedure described by Arias et al. 2016 [45] . The microalgal cultures were centrifuged at 4000 RPM for 6 min in order to separate the precipitated biomass from the supernatant.…”
Section: Methodsmentioning
confidence: 99%